Mesenchymal Stem Cells Conditioned Medium as a Source of Neuroprotective Factors - Székiová, Eva; Slovinská, Lucia; Blaško, Juraj; Čížková, Dáša (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 187